THE CONTENT OF POWER AND GOVERNMENT IN CENTRAL ASIAN NOMADS - Zhusupova Laura Kuandykovna; Torlanbaeva Kenzhe Uskenbaevna; Zhusupov Estay Kuandykovich (Scientific Journal of Pedagogy and Economics, 2020)
The article submitted for publication contains an analysis of the power-management system of Central Asian nomads. The focus of such tasks as: – Analysis of military power, the cult of a warrior in the history of the evolution of the tribal power of the leader in ancient and medieval Central Asia in the context of the theory of chiefdom, neoevolutionism, aggressive and commercial theories of political genesis, evolutionary theories of the matrilinear and patrilineal development of the society; – Study and analysis of the power authority of the tribal power through the system of titles and ranks in the Hunnu, Turkic, Oghuz, Karakhanid, Khitan, Seljuqid states, description and study of the terminology of Chinese texts on ranks and ranks, functions of officials and tribal chiefs, the role of a titled aristocracy in the management system nomadic polities.